The Gastrodia elata genome provides insights into plant adaptation to heterotrophy - Yuan, Yuan; Jin, Xiaohua; Liu, Juan; Zhao, Xing; Zhou, Junhui; Wang, Xin; Wang, Deyi; Lai, Changjiangsheng; Xu, Wei; Huang, Jingwen; Zha, Liangping; Liu, Dahui; et al. (Nature communications, 2018)
We present the 1.06 Gb sequenced genome of Gastrodia elata , an obligate mycoheterotrophic plant, which contains 18,969 protein-coding genes. Many genes conserved in other plant species have been deleted from the G . elata genome, including most of those for photosynthesis. Additional evidence of the influence of genome plasticity in the adaptation of this mycoheterotrophic lifestyle is evident in the large number of gene families that are expanded in G . elata , including glycoside hydrolases and urease that likely facilitate the digestion of hyphae are expanded, as are genes associated with strigolactone signaling, and ATPases that may contribute to the atypical energy metabolism. We also find that the plastid genome of G . elata is markedly smaller than that of green plant species while its mitochondrial genome is one of the largest observed to date. Our report establishes a foundation for studying adaptation to a mycoheterotrophic lifestyle. Gastrodia elata is an obligate mycoheterotrophic plant with highly reduced leaves and bracts in scape. Here, Yuan et al sequence and analyze its 1.06 Gb genome which provides insights in adaptation to a lifestyle of heterotrophy.